HUBUNGAN PENGETAHUAN SIKAP DENGAN TINDAKAN PETUGAS DALAM PENGELOLAAN LIMBAH MEDIS DI KLINIK PRATAMA BADAN NARKOTIKA NASIONAL PROVINSI BALI TAHUN 2024 - Meiyana Sari, Putu Indri; Sali, Wayan; Sujaya, I Nyoman; Rusminingsih, Ni Ketut (Jurnal Kesehatan Lingkungan (JKL), 2024)
Solid medical waste processing is carried out in several stages starting from sorting, collection, storage, transportation and destruction. The purpose of this study was to determine the relationship between knowledge and attitudes with the actions of officers in efforts to manage solid medical waste at the Pratama Clinic of the National Narcotics Board of Bali Province. The type of research is quantitative with an observational method using a cross- sectional design. The population and sample were 63 people with a total sampling method. The instruments were tests and questionnaires. Analysis used Chi square. There is a relationship between knowledge and attitudes with the actions of officers in efforts to manage solid medical waste at the Pratama Clinic of the National Narcotics Board of Bali Province with a p-value of 0.002 0.05. The need for training, socialization, and supervision regarding the management of solid medical waste at the Pratama Clinic of the National Narcotics Board of Bali Province